Estratégias para minimizar os efeitos de um ambiente térmico adverso para frangos de corte: Patrícia Martiniano de Oliveira. - - Oliveira, Patrícia Martiniano de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The heat limits the production of broilers. This study evaluated the interactions between early thermal conditioning (ETC) and the electrolyte balance (EB) on performance and characteristics of birds' carcass. Thus, the electrolyte balance (BE = Na+ + K+ - Cl- ), was set to 350mEq/kg and electrolyte ratio (K+ + Cl- )/ Na+ in 3:1 by PPFR program. The experiment was carried out at the Animal Science department of the Faculty of Veterinary Medicine of Araçatuba / UNESP. It was used 240 male chicks of 1 day old, Cobb-500®, lodged in metal batteries with 24 divisions and automatic electric heating. The experimental design was completely randomized in a factorial arrangement 2x2, totaling 4 treatments with 6 replicates and 10 birds per experimental plot. ETC occurred on the 5th day of age for 24 hours at 36.5 °C in half of the batch. Subsequently, these birds were transferred to an environmentally controlled shed and were grown in boxes, in the same way as the other half that not received ETC treatment. The effects of chronic heat stress (6 hours at 32 °C) applied from the 35th through the 39th day of age were evaluated. Temperature and air humidity, as well black-globe temperature were monitored electronically. Food and water were provided ad libitum. The growth performance data and the mortality rate of birds were measured. The results were subjected to analysis of variance and comparison of means was done by Tukey test. There were no interaction effects between ETC and EB on performance and characteristics of birds' carcass. The strategies ETC and EB proved to be ineffective in order to mitigate the effects of chronic heat stress in broilers
Keywords: Frango de corte; Transtornos de estresse por calor; Ave; Eletrolitos; Equilibrio acido-base; Mortalidade; early thermal conditioning